Social capital dimensions in household food security interventions: implications for rural Uganda - Sseguya, H.; Mazur, R.E.; Flora, C.B. (Springer, 2018)
We demonstrate that social capital is associated with positive food security outcomes, using survey data from 378 households in rural Uganda. We measured food security with the Household Food Insecurity Access Scale. For social capital, we measured cognitive and structural indicators, with principal components analysis used to identify key factors of the concept for logistic regression analysis. Households with bridging and linking social capital, characterized by membership in groups, access to information from external institutions, and observance of norms in groups, tended to be more food secure. Households with cognitive social capital, characterized by observance of generalized norms and mutual trust, were also more food secure than others. However, we established that social capital is, by itself, insufficient. It needs to be complemented with human capital enhancement. We recommend that development interventions which focus on strengthening community associations and networks to enhance food security should support activities which enhance cognitive social capital and human capital skills. Such activities include mutual goal setting, trust building and clear communication among actors. Education efforts for community members, both formal and non-formal, should also be supported such that they potentially strengthen social capital to improve food security in rural Uganda.